Plant Developmental Biology Methods and Protocols - Hennig, Lars.; Köhler, Claudia; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2010)
The beauty and variety of plants has fascinated mankind for thousands of years, and this fascination continues today as plant developmental biologists discover mechanisms that control the establishment of specialized cell types, tissues, and organs from the fertilized egg during a plant’s life. In Plant Developmental Biology: Methods and Protocols, expert researchers provide a collection of protocols for many of the common experimental approaches in plant developmental biology, including diverse methods that range from grafting over bimolecular fluorescence complementation to chromatin immunoprecipitation. Chapters are divided into six major parts: growth protocols, manipulation of gene activity, assaying developmental phenotypes, assaying gene activity, testing protein-protein interactions, and probing chromatin. Composed in the highly successful Methods in Molecular Biology™ series format, each chapter contains a brief introduction, step-by-step methods, a list of necessary materials, and a Notes section which shares tips on troubleshooting and avoiding known pitfalls. Comprehensive and revolutionary, Plant Developmental Biology: Methods and Protocols is an essential guide for all plant developmental geneticists, biochemists, and researchers in stress physiology and plant nutrition.
Growth Protocols for Model Plants in Developmental Biology -- Grafting as a Research Tool -- Virus-Induced Gene Silencing as a Reverse Genetics Tool to Study Gene Function -- The CRE/lox System as a Tool for Developmental Studies at the Cell and Tissue Level -- Inducible Gene Expression Systems for Plants -- Trichome Development in Arabidopsis -- Phenotyping the Development of Leaf Area in Arabidopsis thaliana -- Analyzing Shoot Apical Meristem Development -- Analyzing Floral Meristem Development -- Female Gametophytic Mutants: Diagnosis and Characterization -- Pollen Tube Development -- Analysis of Root Meristem Size Development -- Phenotypic Characterization of Photomorphogenic Responses During Plant Development -- Kinematic Analysis of Cell Division and Expansion -- Flowering Time Control -- mRNA Detection by Whole Mount In Situ Hybridization (WISH) or Sectioned Tissue In Situ Hybridization (SISH) in Arabidopsis -- Immunolocalization of Proteins in Plants -- Detection of Small Non-coding RNAs -- Quantitative Real Time PCR in Plant Developmental Biology -- Luciferase and Green Fluorescent Protein Reporter Genes as Tools to Determine Protein Abundance and Intracellular Dynamics -- Fluorescence-Activated Cell Sorting in Plant Developmental Biology -- Laser Microdissection of Paraffin-Embedded Plant Tissues for Transcript Profiling -- Utilizing Bimolecular Fluorescence Complementation (BiFC) to Assay Protein–Protein Interaction in Plants -- The Split Luciferase Complementation Assay -- Co-immunoprecipitation and Protein Blots -- Probing Protein–Protein Interactions with FRET–FLIM -- Plant Chromatin Immunoprecipitation -- Immunocytological Analysis of Chromatin in Isolated Nuclei -- Bisulphite Sequencing of Plant Genomic DNA.
Keywords: Plant science; Botany; Plant genetics; Developmental biology; Plant Sciences; Plant Genetics and Genomics; Developmental Biology